1917
DOI: 10.1084/jem.25.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Metabolism of Cells in Vitro

Abstract: A synthetic medium suitable for the growth of tissue cells outside of the animal organism has not been discovered up to the present time. Since the preparation of such a medium would lead directly to a better understanding of cellular metabolism, this problem has stood forth as one of the most important of those presented by the tissue culture method.From earlier observations evidence had already been obtained which showed that the ingredients essential for the building of new cells and the liberation of energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1924
1924
1947
1947

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Summary.- (1) The hitherto unknown urea alkyl sulfates are described. (2) It has been shown that the main reaction products of alcohols with sulfuryl chloride are alkyl hydrogen sulfates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Summary.- (1) The hitherto unknown urea alkyl sulfates are described. (2) It has been shown that the main reaction products of alcohols with sulfuryl chloride are alkyl hydrogen sulfates.…”
mentioning
confidence: 99%
“…BzNHCHoN-C(CH.,)5COOH BzNHCH2C(CH2)4COOH H _____I II(1) J. P. English and R. C. Clapp, This Journal,67, 2262 (1945).…”
mentioning
confidence: 99%
“…BzNHCHoN-C(CH.,)5COOH BzNHCH2C(CH2)4COOH H _____I II(1) J. P. English and R. C. Clapp, This Journal,67, 2262 (1945).…”
mentioning
confidence: 99%